Engineered bacteria detect spatial profiles in glucose concentration within solid tumor cell masses. Issue 11 (20th September 2016) - Panteli, Jan T.; Forbes, Neil S.
ABSTRACT: Tumor heterogeneity makes cancer difficult to treat. Many small molecule cancer drugs target rapidly dividing cells on the periphery of tumors but have difficulty in penetrating deep into tumors and are ineffective at treating entire tumors. Targeting both rapidly dividing and slower growing regions of tumors is essential to effectively treat cancer. A cancer drug carrier that penetrates deep into tumors and identifies metabolically activity could supply treatment to those areas based on the local microenvironment. We hypothesized that glucose sensing bacteria could identify sugar gradients in solid tumors. To test this hypothesis, a genetic circuit was designed to trigger expression of a green fluorescent protein (GFP) reporter through the chemotaxis‐osmoporin fusion protein, Trz1, a receptor for sensing glucose and ribose sugars. E. coli equipped with the Trz1‐GFP expression system, were administered to an in vitro model of a continuously perfused tumor tissue that mimics systemic delivery and clearance of bacteria through a blood vessel adjacent to a solid tumor. The level of GFP expressed, per bacterium, was time independent and indicated the glucose concentration as a function of penetration depth within the microfluidic tumors. The measured glucose concentration, correlated ( P ‐value = 2.6 × 10 −5 ) with tumor cell viability as a function of depth. Mathematical analysis predicted drug delivery by glucose‐sensing bacteria would eliminate a higher percentage of the viable tumor cell population than a systemically administered drug. Glucose‐sensing bacteria could deliver cancer therapies with increased drug penetration and nutrient‐dependent dosing to continuously treat viable regions of cancer tissue that have a higher prevalence for metastatic dissemination. Biotechnol. Bioeng. 2016;113: 2474–2484. © 2016 Wiley Periodicals, Inc.